Analisis Faktor-Faktor Dampak Bahaya Stunting di Kawasan Masjid Al Akbar Surabaya - Fierda Nurany; Chairien Nurwulan Ghozalyfah; Fajar Rachma Dian; Ferdian Iqbal; Dhurrotul Machbubah; Laila Della Amanda (Program Studi Administrasi Publik Universitas Muhamamdiyah Bengkulu, 2023)
The purpose of this study is to determine public understanding of the dangers of stunting in the Al-Akbar Mosque area of Surabaya and the components that affect it. This research uses a qualitative approach with a descriptive approach. The community around Masjid Al-Akbar Surabaya, health institutions, institutions of women's empowerment and child protection, population control and family planning, and other sources of information are the subjects of this study. The source of research data is informants. Observations and interviews were used in this study. The results show that people still have a low understanding of stunting, and many people do not know how to prevent it, as well as the biological, environmental, economic, and social impacts of stunting. Studies conducted in the Al Akbar Mosque area of Surabaya show that people do not understand the dangers of stunting and how to prevent it. Influencing factors include: Child nutrition, too much instant food, poor motherhood, weak immunity and so on. Therefore, the importance of stunting prevention and treatment with a comprehensive approach